Elemen-Elemen Demokrasi dalam Pemikiran Jürgen Habermas: Elements of Democracy in Jurgen Habermas' Thought - Hendrawan, Datu; Adinda S., Anastasia Jessica (Jurnal Filsafat Indonesia, 2025)
The decline in the democracy index in Indonesia and the symptoms of weakening democracy throughout the world are urgent matters to respond to. In 2024, Indonesia is categorized as a country that is included in the category of flawed democracy based on a survey by The Economist Intelligence Unit (EIU). Based on the Lexical Index of Electoral Democracy (LIED), out of 199 countries, only 40% have a democratic system with guaranteed voting rights and freedom of assembly and opinion. This situation needs to be analyzed. An understanding of democracy and its underlying elements is required to analyze the issue. A philosophical approach is needed to formulate the basic elements of democracy. These elements can be used to analyze and examine the problem of the crisis of democracy. A philosopher who has quite comprehensive thoughts on democracy is Jurgen Habermas. In this study, the researcher intends to examine the basic elements of democracy according to Habermas’s ideas and find their relevance in dealing with the current crisis of democracy. This study uses a literature study method, which focuses on interpretation and analysis of texts. Jurgen Habermas's thinking can provide a comprehensive picture of the fundamental elements of democracy. These elements are the existence of public sphere, civil society, communicative action, synergistic links between the system and the life world, public discourse, and the decision-making process through rational deliberation. The completeness of these elements will further strengthen the building of democracy. Reconstruction of democracy can be done by re-examining the completeness and integrity of the conditions of these elements to be improved.